Olympia, Griechenland: Das Leonidaion - Mächler, Claudia (e-Forschungsberichte des DAI, 2023)
At over 6000 square meters (74,1 m × 81,08 m), the Leonidaion is the largest preserved building at Olympia and is the focus of an ongoing building survey, which began as a dissertation project in May 2014. This well-known, important structure to the southwest of the Altis was funded by Leonides of Naxos in about 330 BC. The first German excavations from 1878 until 1881 uncovered its northern portion, and the southern part was excavated from 1954 until 1956 under the overall direction of Emil Kunze. Despite its unique design and its long and eventful history of renovation, the Leonidaion has otherwise remained unstudied. This project will provide the systematic, scientific building survey, which has been lacking.